A comparative study on the accuracy of small-signal equivalent circuit modeling for large gate periphery GaN HEMT with different source to drain length and gate width. (December 2021) - Anand, Anupama; Reeta,; Rawal, Dipendra Singh; Narang, Rakhi; Mishra, Meena; Saxena, Manoj; Gupta, Mridula
Abstract: In this paper, extrinsic and intrinsic parameters were extracted from the experimental S-parameters using 16- and 22-element small signal equivalent circuit model for large gate periphery GaN HEMT with different source to drain length and gate width over 500 MHz to 26 GHz range. The extraction using 22-element model shows good consistency to measured S-parameters and the maximum gain, stability factor, delta factor and K-factor with less percentage error than 16-element model. As the source to drain length is increasing, the accuracy of parameter extraction is enhanced for 22-element model. Specially for stability factor and K-factor the percentage error was reduced drastically (10.42%–4.74% and 8.13%–0.83% respectively). For increased number of fingers, the 22-element model shows more accuracy. Also, TCAD (Technology Computer-Aided Design) device simulations were done and transfer characteristic were calibrated with measured data. The simulated s-parameters were then calibrated with the experimental extrinsic parameters.